PENGARUH PUPUK KANDANG KAMBING DAN PUPUK NPK TERHADAP PERTUMBUHAN DAN HASIL CABAI RAWIT ( Capsicum frutescens L. ) UMUR 100 HARI: Kata kunci: Pupuk NPK, Cabai Rawit, pupuk kandang kambing - Mukti Fajar; Sartono Joko Santosa; Siswadi Siswadi (FAKULTAS PERTANIAN UNIVERSITAS SLAMET RIYADI, 2022)
Effect of dose of NPK fertilizer and goat manure on growth and yield of cayenne pepper (Capsicum frutescens L.) aged 100 days. Conducted at the Experimental Garden of the Faculty of Agriculture, Slamet Riyadi University, Surakarta on November 22, 2021 – March 2, 2022. The purpose of this study was to determine the effect of goat manure and NPK on growth and yield of 100-day-old cayenne pepper (Capsicum frutescens L.). This study used a completely randomized design (CRD) with 2 factors and 3 replications. The two factors are NPK fertilizer (N) with 4 levels, namely: control (N0), dose of 2.5 grams/polybag (N1), dose of 5 grams/polybag (N2), dose of 7.5 grams/polybag (N3), goat manure consisting of 4 levels, among others: control (K0), a dose of 80 grams/plant (K1), a dose of 160 grams/plant (K2), a dose of 240 grams/plant (K3). The results showed that the application of NPK (N) fertilizer had an effect on when flowers appeared and fruit diameter was the fastest at 49.00 and the largest fruit diameter was 1.00 cm. The application of goat manure (K) did not affect all observations. The interaction between the application of NPK fertilizer (N) and goat manure (K) did not affect all parameters